The geo‐historical legacies of urban security governance and the Vancouver 2010 Olympics. Issue 3 (20th March 2014) - Molnar, Adam
<x xml:space="preserve">Abstract</x> In 2004, the discourse of 'legacy' was woven into the constitutional fabric of the International Olympic Committee (IOC). Bidding for Olympic events is now premised on procuring post‐event legacies that will resonate through local communities and host countries long after the flame is extinguished. Given vast expenditures in security, policing, and emergency management operations at major sporting events, it is notable that the IOC and its official partners have disproportionately under‐represented security and policing legacies. This paper addresses research into security and policing legacies of major events by turning much needed empirical attention towards institutional‐level geographies of security and policing – particularly on legacies of policing and militarisation in Olympic host cities. Accordingly, the paper traces the institutional trajectory of the Military Liaison Unit (MLU) in the Vancouver Police Department who were heavily involved in coordinating the joint civilian–military effort throughout the lifecycle of the Vancouver 2010 Winter Games. Theoretically, the paper furthers Stephen Graham's (2010) New Military Urbanism that considers the circulation of military expertise between neo‐colonial frontiers of military intervention with Western urban spaces. In doing so, this paper unpacks an empirically guided temporal approach that discerns key drivers of militarisation as localised, empirical‐based 'trajectories' of development of security and policing institutions, which are linked to, and circumscribed by, critical juncture episodes in the context of mega event security. The paper traces processes of the MLU to explain how conditions underpinning the civil–military divide in urban policing, as a series of jurisdictional, institutional, and by extension, geographical configurations have continued, changed or been abandoned in the context of the Vancouver 2010 Olympics. As such, this paper contributes to much needed debate on the controversies and opportunities inherent in security legacies and major events, which implicate the wider securitisation and militarisation of Western cities.